Coherence in neutrino oscillations - Ilmavirta, Joonas (2011)
The theory of neutrino oscillations has turned out to be the most reasonable explanation to the observed violations in lepton number conservation of solar and atmospheric neutrino fluxes. A derivation of the most important results of this theory is first given using a plane wave treatment and subsequently using a three-dimensional shape-independent wave packet approach. Both methods give the same oscillation patterns, but only the latter one serves as a decent starting point for analyzing coherence in neutrino oscillations.